Bahasa Inggris - Sri Marwiyati; M. Aminudin (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
This research aims to analyze the implementation of the Merdeka Curriculum at Tarbiyatul Banin 19 Salatiga Islamic Kindergarten in forming Pancasila students in childhood education. It uses descriptive qualitative methods, with data collected through interviews with the principal and teachers, classroom observations, and document analysis related to the Merdeka Curriculum. Data were analyzed using Mile and Huberman’s approach, which involves data collection, reduction, presentation, and conclusion. The results show that the supporting factors for implementing the Merdeka Curriculum at TK Tarbiyatul Banin 19 include the availability of clear curriculum guidelines, adequate media and educational tools (APE), and positive support from parents and the surrounding society. In addition, student participation in daily activities at school helps shape the Pancasila student profile. However, implementing this curriculum also faces challenges, such as teachers' limited experience in applying the Merdeka Curriculum and differences in teachers' understanding of the concrete application of the Pancasila character. This research emphasizes the essentiality of enhancing teacher capacity and fostering collaboration between schools, families, and communities to reinforce the development of the Pancasila profile in early childhood education.